TINGKAT KEASINAN DAN UJI ORGANOLEPTIK TELUR AYAM RAS DENGAN WAKTU PERENDAMAN YANG BERBEDA - Umbang Arif Rokhayati; Soegeng Herijanto (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2021)
The purpose of this study was to determine the organoleptic value of salty taste in eggs soaked in salt solution with different soaking times. The materials used in this study were 90 eggs, rubbing ash and crust salt (table salt). The experimental design used was a completely randomized design (CRD) with 3 treatments and 3 replications. The parameters observed in this study were the organoleptic value and salinity level. The results showed that the duration of soaking eggs in a salt solution had a significant effect on the organoleptic value and salinity of the eggs (P 0.05) on the organoleptic value and the salinity level of the panelists preferred the results of soaking in a salt water solution with a long soaking time of 12 days.